Ma'na-cum-Maghza Approach to the Qur'an: Interpretation of Q.S. 24: 32-33 on the Precaution of Self-Preservation - Hubby Dzikrillah Alfani, Ilzam; Mukhsin, Mukhsin; Fadllurrahman, Irfan; Fajar Firdaus, Zhilal (Universitas Islam Negeri Imam Bonjol Padang, 2024)
The purpose of this study is to examine the differing interpretations among Islamic scholars regarding Q.S. 24:33. While the majority of classical and contemporary exegetes agree that Q.S. 24:32 commands marriage for single individuals, there is a divergence of opinion concerning Q.S. 24:33. Most scholars argue that if one is unable to marry, they should maintain chastity until Allah grants them sufficiency. In contrast, Abu Ja'far Muhammad bin Jarir al-Tabari and Ibn Mas'ud interpret this verse as an indication to hasten marriage, even in conditions of poverty, suggesting that family members should provide financial assistance to facilitate the marriage. This approach is highly recommended for single individuals, as marriage is considered more effective in preserving chastity than fasting. Therefore, this study tries to read the content of Q.S. 24: 32-33 with Ma'na-cum-Maghza theory as an approach to answer contemporary problems. This research is qualitative in nature with the type of data written in the form of primary data, namely Q.S. 24: 32-33 about the recommendation to marry and protect themselves and secondary data in the form of hadith, tafsir from classical to contemporary centuries, books, journals, theses-dissertations, and the web that can help run the research. This research produces answers in the form of first, the content of Q.S. 24: 32-33 by analyzing the linguistics of several key words shows that these two verses are not only a matter of marriage and self-preservation, but also concern personal issues and characteristics. Second, Q.S. 24: 32-33 as an affirmation of marriage is a very noble worship that includes a very correct way to control one's lust because it can be channeled with a legal partner and avoid things that are prohibited by religion and the state. Third, Q.S. 24: 32-33 if drawn in the context of today as a reference for people who want marriage to be able to afford and prepare various pre- and post-marriage requirements that must be met. Financially in the form of property, dowry, reception fees, costs of life after marriage (nafkah). Psychologically in the form of readiness for the science of marriage, mental readiness, readiness to meet the physical and mental needs of the family.